2006
DOI: 10.1172/jci25303
|View full text |Cite
|
Sign up to set email alerts
|

Loss of constitutive activity of the growth hormone secretagogue receptor in familial short stature

Abstract: The growth hormone (GH) secretagogue receptor (GHSR) was cloned as the target of a family of synthetic molecules endowed with GH release properties. As shown recently through in vitro means, this receptor displays a constitutive activity whose clinical relevance is unknown. Although pharmacological studies have demonstrated that its endogenous ligand -ghrelin -stimulates, through the GHSR, GH secretion and appetite, the physiological importance of the GHSR-dependent pathways remains an open question that gives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
203
0
18

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(229 citation statements)
references
References 44 publications
8
203
0
18
Order By: Relevance
“…to French reference values) was found to carry the Ala204Glu mutation in the homozygous state; whilst the parents were heterozygous for this mutation (maternal and paternal height was noted to be 2.7SD and 3.7SD below the mean, respectively). In addition, several members of family 1 were overweight or obese -BMI of the 13 year old proband was 26.2kg/m 2 (Pantel et al, 2006). In family 2, the 11 year old female proband was found to carry the same mutation in the heterozygous state, and the affected father (height 2SD below mean) was also heterozygous for the mutation (Pantel et al, 2006).…”
Section: Ghs-r Mutations In Patientsmentioning
confidence: 98%
See 2 more Smart Citations
“…to French reference values) was found to carry the Ala204Glu mutation in the homozygous state; whilst the parents were heterozygous for this mutation (maternal and paternal height was noted to be 2.7SD and 3.7SD below the mean, respectively). In addition, several members of family 1 were overweight or obese -BMI of the 13 year old proband was 26.2kg/m 2 (Pantel et al, 2006). In family 2, the 11 year old female proband was found to carry the same mutation in the heterozygous state, and the affected father (height 2SD below mean) was also heterozygous for the mutation (Pantel et al, 2006).…”
Section: Ghs-r Mutations In Patientsmentioning
confidence: 98%
“…In addition, several members of family 1 were overweight or obese -BMI of the 13 year old proband was 26.2kg/m 2 (Pantel et al, 2006). In family 2, the 11 year old female proband was found to carry the same mutation in the heterozygous state, and the affected father (height 2SD below mean) was also heterozygous for the mutation (Pantel et al, 2006).…”
Section: Ghs-r Mutations In Patientsmentioning
confidence: 98%
See 1 more Smart Citation
“…This ligand-independent activity was recently proven to be an intrinsic feature of the GHSR protein and not merely the consequence of an influence of the cellular environment [42]. The constitutive activity of GHSR appears to be important in humans, since a missense mutation of the GHSR, which leads in the loss of the constitutive activity of the receptor while retaining its ability to respond to ghrelin-induced signaling, resulted in familial short stature [43]. In light of this knowledge, we wondered whether the constitutive activity of GHSR needed to be reduced to attenuate seizure activity.…”
Section: Inverse Agonism Of Ghsr Is Anticonvulsant In In Vitro and Inmentioning
confidence: 99%
“…In mice, loss of function of the GHSR gene is associated with lower insulin-like growth factor 1 concentrations and a lower body mass in adult animals that is independent of food intake and energy expenditure. 4 In humans, Pantel et al 19 found a mutation of the GHSR gene in two families in which short stature was inherited in a dominant manner. In keeping with a dominant inheritance with variable penetrance, short stature was present in the proband, who was homozygous for the mutation, and in some of the family members who were heterozygous for the mutation.…”
Section: Ghrelin Gh Ghsr and Linear Growthmentioning
confidence: 99%